Impact of land and forest fire on soil fauna diversity in several land cover in Jambi Province, Indonesia - BASUKI WASIS; BAYU WINATA; DANIEL RICARDO MARPAUNG (Biodiversitas Journal of Biological Diversity, 2018)
Wasis B, Winata B, Marpaung DR. 2018. Impact of land and forest fire on soil fauna diversity in several land cover in Jambi Province, Indonesia. Biodiversitas 19: 740-746. Forest fire is one of the primary disturbances that damage forest and disturb forest sustainability. Land and forest fire may lead to die-offs, declines and in general influence the development of abundant of soil fauna on the ground. This research aims to identify and assess the diversity, wealth, evenness, and the pattern and spread of land fauna in various ecosystems, both burnt and unburnt by the fire. Research was conducted in some districts in Jambi Province, Indonesia. Sampling methods for soil diversity were done by hand-sorting methods in three burnt and unburnt ecosystems. Those ecosystems were primary forest, industrial plantation forest, and oil palm plantation. Generally, we found 519 individual species included in 46 genera, 33 families, 20 orders of 8 classes, and 3 phyla in whole ecosystem observed. The highest soil fauna diversity was primary forest with value of DMg = 4.243, H'=2.664, E=0.862. Meanwhile, the lowest soil fauna diversity was found in burnt palm plantation with value of DMg=2.102, H'=1.520, and E=0.692. Environmental factors like abiotic and biotic affected to the diversity level of soil fauna.